2013
DOI: 10.1152/ajpendo.00401.2013
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular lipid content is a key intrinsic determinant for hepatocyte viability and metabolic and inflammatory states in mice

Abstract: Sheng L, Jiang B, Rui L. Intracellular lipid content is a key intrinsic determinant for hepatocyte viability and metabolic and inflammatory states in mice. Am J Physiol Endocrinol Metab 305: E1115-E1123, 2013. First published August 27, 2013 doi:10.1152/ajpendo.00401.2013The liver is an essential metabolic organ. In addition to metabolizing glucose and lipids, hepatocytes also secrete various cytokines that modulate both hepatocyte metabolism and liver inflammation. Hepatocyte injury and death and liver infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…Substantive organ inflammatory disease generally involves extensive parenchymal cell injury, which is considered to be involved in regulation of inflammation 6 31 32 33 34 . It has been described that hepatocytes are involved in ethanol-induced liver injury by releasing the endogenous danger molecules, uric acid and ATP, which are recognized by liver immune cells 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantive organ inflammatory disease generally involves extensive parenchymal cell injury, which is considered to be involved in regulation of inflammation 6 31 32 33 34 . It has been described that hepatocytes are involved in ethanol-induced liver injury by releasing the endogenous danger molecules, uric acid and ATP, which are recognized by liver immune cells 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Liver injury, usually induced by heavy alcohol consumption, drug abuse, and virus infection, is a common clinical disease characterized by hepatocyte injury 3 4 5 . Recently, many studies have shown that injured hepatocytes can secrete important cytokines and chemokines that are involved in the immune response, by activating and recruiting immunocytes 2 6 7 . Although the cytokines and chemokines secreted by injured hepatocytes have been considered to participate in liver injury 6 , the molecular mechanism of how these cytokines and chemokines are produced from injured hepatocytes is still indistinct.…”
mentioning
confidence: 99%
“…Values are presented as means Ϯ SE. *P Ͻ 0.05. bone marrow-derived macrophages (BMDMs) as described previously (22). BMDMs were treated without or with LPS (20 ng/ml) for 4 h and washed extensively with PBS and cultured in fresh growth medium.…”
Section: Animalsmentioning
confidence: 99%
“…Hepatocytes, which are major parenchymal cells in the liver, play pivotal roles in metabolism, detoxification, and protein synthesis. Hepatocytes can accumulate triglyceride by increasing fatty acid uptake and de novo lipogenesis, and metabolize fatty acids through lipolysis [13]. Kupffer cells, the resident macrophage in the liver, play an integral role in the hepatic immune response [14].…”
Section: Pathogenesis Of Nafld and Progression To Nash Fibrosis Andmentioning
confidence: 99%